Physicochemical Baseline and Thermal Pollution of Canal Water Adjacent to the Barapukuria Coal Mine, Dinajpur, Bangladesh - Najmun Nahar; Woindrila Rani Sarker; Md. Mohiuddin; Neegar Sultana; Farhan Ahmed Rafid; Arafat Hossain (Sriwijaya Journal of Environment, 2026)
Background: Untreated effluent from the Barapukuria coal mine, the only operating underground coal mine in Bangladesh, enters adjacent canals used by local communities, yet no station-resolved baseline exists for the receiving canal. Objective: This study established a pre-monsoon (March 2023) physicochemical baseline of the canal in Dinajpur, northern Bangladesh, to evaluate compliance with the Bangladesh Environment Conservation Rules (ECR) 1997 and World Health Organization (WHO) guidelines. Methods: Five stations (W1 upstream to W5 downstream) were sampled at 200 m intervals and measured in triplicate for temperature, colour, odour, pH, dissolved oxygen (DO), electrical conductivity (EC) and total dissolved solids (TDS); data were analysed using one-way ANOVA, Tukey HSD, Pearson correlation, principal component analysis (PCA) and a weighted-arithmetic Water Quality Index (WQI). Results: pH (7.08 ± 0.34), DO (5.16 ± 1.55 mg L-1) and TDS (430 ± 125 mg L-1) remained within limits, whereas temperature peaked at 31.7 °C, exceeding the 28 °C ECR aquatic-life limit, and EC fell to 176 µS cm-1, indicating mineral-poor water. All parameters differed among stations (p < 0.001; η2 = 0.94–0.99); PCA explained 92.1% of variance and isolated the discharge point; WQI (66.1–81.5, “Good”) deteriorated downstream. Conclusion: The canal is chemically compliant but thermally stressed and mineral-poor, warranting industrial cooling, sedimentation control and multi-season monitoring to protect downstream aquaculture and agriculture.